Morfologia e anatomia de frutos e sementes da tribo Willughbeieae (Apocynaceae, Rauvolfioideae) - Mello, Carolina Carvalho de, 1986- (2013)
Orientadores: André Olmos Simões, Sandra Maria Carmello Guerreiro